Wandering hero, wandering myths? The image of Heracles in Iran - Wood, R (De Gruyter, 2018)
Highlighting the fact that ancient societies were linked by their shared use of mythological narratives, Wandering Myths aims to advance our understanding of the mechanisms by which such tales were disseminated cross-culturally and to ...